If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -7n = -5 Solving -9 + -7n = -5 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -7n = -5 + 9 Combine like terms: -9 + 9 = 0 0 + -7n = -5 + 9 -7n = -5 + 9 Combine like terms: -5 + 9 = 4 -7n = 4 Divide each side by '-7'. n = -0.5714285714 Simplifying n = -0.5714285714
| -3(-2g+16)= | | .75x-.33x=9 | | -2(-8+3c)= | | 3(g+3)=24 | | 3(10)-5y=20 | | (5u-3)(4+u)=0 | | 7-2(-5x-9)+2x=4(2x-1)+3x+2 | | -11(16-13z)= | | 9-9r=-8 | | 15+3z=39 | | -6-3x=40-5x | | -4(-6-16k)= | | -35y=20 | | 3x+4(3x-53)=7 | | 5x-(2x-9)=18 | | 18(-6p-7)= | | 17x-5+80=180 | | -2x-4=-3x+3 | | 5x^3-25x^2+35x=0 | | -0.75n+4=-2 | | -w+102=208 | | .5x=-(-8) | | -6(7x+5)=7 | | N^2+2n=5n+15 | | 3x+9=12x-18 | | 3x+109=8x-174 | | 39=294-v | | 3-8(7-5b)= | | -13(4r+6)+9r= | | 8x+9y=1 | | x+63=55 | | 0=-16t^2+48t+0 |